Mechanisms Mediating Bradycardia during Coronary Arteriography - Eckberg, Dwain L. (1974)
Cardiac slowing occurring during diagnostic coronary arteriography was studied in 78 patients. Comparable degrees of slowing occurred with injections into the right and into the left coronary arteries into the contralateral artery, and with injections into the coronary artery giving rise to the sinus node artery and into the contralateral artery. Rapid intracoronary injections of isosmotic dextrose solution produced significantly less slowing than comparable injections of contrast medium. Slow injections of contrast medium produced cardiac slowing comparable to that caused by rapid injections of contrast medium. However, the cardiac slowing was significantly greater than that produced by rapid injections of dextrose solution. Inhalation of 100% oxygen did not alter the heart rate response to injections of contrast medium. Atropine produced dose-related attenuation of cardiac slowing. Bradycardia persisting after cholinergic blockade was significantly greater after injections into the coronary artery supplying the sinus node than it was after injections into the contralateral artery. Coronary arteriography produced transient, occasionally profound, arterial hypotension in 38 of 41 patients in whom arterial pressures were recorded. Arterial pressure did not change in three patients. This study suggests that the cardiac slowing which occurs during coronary arteriography in man is due primarily to a cholinergic reflex which may be a human counterpart of the Bezold-Jarisch reflex, observed heretofore only in experimental animals. This slowing appears to be mediated primarily by receptors sensitive to contrast medium, rather than by changes of coronary artery pressure, and secondarily, by direct depression of sinus node function by contrast medium.